The service-stock trap: analysis of the environmental impacts and productivity of the service sector in Hungary. (21st June 2019) - Dombi, Mihály
Abstract: Urbanization and the emerging share of the service sector in economic output may support the sustainability transition due to lower material input and emissions, while further accelerating the economic growth at the same time. Nevertheless, there are significant barriers to the transition. In this study, the service sector of Hungary and its four commercial sub-sectors have been analyzed with regard to their material requirement (input flows and stock) and greenhouse gas emissions (GHG) emissions utilizing EXIOBASE v3. General policy implications are also provided with special regard to costs, possible taxes and productivity of resources. The share of direct and indirect GHG emissions and material input generated by the sector was stable and moderate. A permanently improving trend is present in GHG, and material input intensity. Material stock accumulation in the service sector (capital stock), however, shows an ascending trend, and it has increased from 42% in 1995 to be 55% in 2015. Material input productivity of investments into services has increased until the economic crisis, then it starts to decline or stagnate; while overall stock productivity has decreased in two sub-sectors, and slow improvement was observable in sub-sectors of transportation and information and communication technology (ICT). Stock productivity of ICT and machinery capital stock was decreased dramatically in all sub-sectors. Four economic sub-sectors of the commercial services analyzed in this study have increased their capital stock from 130 to 288 Mt between 2000 and 2015. The exponential trend in material stock accumulation is an environmental issue with rising scientific concern and awareness, since it constitutes the basis of crucial waste management, resource scarcity and resource use challenges in the future. The current study indicates general reinforcement of the environmental pressure of material stock accumulation by the service sector. This phenomena was defined as the 'service-stock trap', which refers to the sign of a trade-off between the descending flow-type environmental impacts and ascending impacts of capital stock accumulation during the economic transition towards a service-based economy. As a promising way out of the trap, the resource tax was discussed in detail, which seems to be suitable for forming investment decisions of the business actors.